Introduction: "What is Meaning in a Legal Text?" A First Dialogue for Law and Linguistics - Judith N. Levi (Washington University Law Quarterly, 1995)
This Article begins by describing the development of interest within linguistics over the last two decades in the language of legal processes, continues by tracing the evolution of the conference from a 1993 collaborative research project carried out by one law professor and three linguists, and concludes with some personal observations of the author on the benefits that linguists like herself stand to gain from further interdisciplinary efforts in this domain.
Keywords: Meaning; Law and linguistics